Analysis of the Effect of Training and Motivation on Organizational Commitments and Its Impact on Employee Performance (Study on Insurance Marketing Agents on Prudential Agency Pru-Aini Gunung Sitoli PT) - Marunduri, Pinces; Heryanto, Heryanto (Archives of Business Research, 2019)
This research was conducted to find out and analyze the effect of training and motivation and organizational commitment on the performance of Insurance Marketing Agents at Pru-Aini Prudential Agency Gunung Sitoli PT. The research method used is a quantitative approach with path analysis method. Data collection techniques with questionnaires, observation and interviews The population of this study amounted to 500 employees. The sampling technique uses propotional random sampling so that the sample is 220 people. The results of this study found that direct training did not significantly influence commitment. Organizational, motivation directly has a significant effect on organizational commitment. Direct organizational commitment has a significant effect on performance. Training directly does not have a significant effect on performance. Direct motivation does not have a significant effect on performance, directly training through organizational commitment has a significant influence on performance and indirectly motivation through organizational commitment has a significant influence on the performance of Insurance Marketing Agents at Pru-Aini Prudential Agency Gunung Sitoli PT.